2020
DOI: 10.3390/foods9030324
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Bioactive Peptide with Antimicrobial Properties Produced by Saccharomyces cerevisiae

Abstract: A variety of organisms produce bioactive peptides that express inhibition activity against other organisms. Saccharomyces cerevisiae is considered the best example of a unicellular organism that is useful for studying peptide production. In this study, an antibacterial peptide was produced and isolated from Saccharomyces cerevisiae (Baker’s yeast) by an ultrafiltration process (two membranes with cut-offs of 2 and 10 kDa) and purified using the ÄKTA Pure 25 system. Antibacterial peptide activity was characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Food-grade production of Leg1 could be achieved by chemical synthesis or by the chymotryptic digestion of chickpea storage proteins. In addition to chemical synthesis or enzymatic hydrolysis of food proteins, biotechnological processes, which are often rather cost-effective, can also be considered for large-scale production [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Food-grade production of Leg1 could be achieved by chemical synthesis or by the chymotryptic digestion of chickpea storage proteins. In addition to chemical synthesis or enzymatic hydrolysis of food proteins, biotechnological processes, which are often rather cost-effective, can also be considered for large-scale production [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces boulardii CNCMI-745 showed significant and beneficial antimicrobic effect against infectious and bacterial pathogens like Vibrio cholerae, Salmonella, C. difficle, E. coli, Shigella, Retrovirus and Candida albicans using cellular and animal models [43] . The antimicrobial peptides which are formed by the yeast cells are very effective in their antagonistic activity because of the electrostatic reaction that occurs inside the cell membranes [44] . Antimicrobial peptides produced by Saccharomyces cerevesiae decreased the survivability of B. subtilis, E. coli, K. aeruginosa, S. aureus when equated to control strain.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The peptide/free amino acid ratio, as well as protein contents and leakage degree, vary according to the extraction methodology (Rakowska et al., 2017; Takalloo et al., 2020). In vitro and in vivo assays have demonstrated that yeast extracts obtained from S. cerevisiae strains by different methodologies contain a set of peptides exhibiting distinct bioactivities (Table 1) as follows: anti‐hypertensive (Alcaide‐Hidalgo et al., 2007; Amorim et al., 2019; He et al., 2012; Hu et al., 2014; Kanauchi et al., 2005; Kohama et al., 1990; Mirzaei et al., 2015;); antimicrobial (Al‐Sahlany et al., 2020; Branco et al., 2014, 2015; Branco, Francisco, et al., 2017; Branco, Kemsawasd, et al., 2017; Fakruddin et al., 2017; Guilloux‐Benatier & Chassagne, 2003; Rizk et al., 2018); anti‐diabetes (Edens et al., 2002; Hu et al., 2014; Jung et al., 2011); anti‐obesity (Jung et al., 2012); mitogenic (Hassan, 2011); immunomodulatory (Yu et al., 2002), and antioxidant (Alcaide‐Hidalgo et al., 2007; Hassan, 2011; Hu et al., 2014; Jung et al., 2011; Mirzaei et al., 2015) (Figure 1) . Many of these bioactivities have been attributed to 22 bioactive specific amino acid sequences containing 2, 3, or 4 amino acid residues or oligopeptide short chains composed of up to 25 amino acid residues.…”
Section: Metabolic Enzymes and Stress‐enrolled Proteins As Potential ...mentioning
confidence: 99%
“…To understand the link between bioactive peptide release and protein‐encoding gene expression modulation during yest biomass propagation, an extensive search for bioactive peptides from Saccharomyces cerevisiae extracts and their diversified previously described biological effects was carried out herein and presented in Table 1 (Al‐Sahlany et al., 2020; Alcaide‐Hidalgo et al., 2007; Amorim et al., 2019; Branco et al., 2014, 2015; Branco, Francisco, et al., 2017; Branco, Kemsawasd, et al., 2017; Edens et al., 2002; Fakruddin et al., 2017; Guilloux‐Benatier & Chassagne, 2003; Hassan, 2011; He et al., 2012; Hu et al., 2014; Jung et al., 2011, 2012; Kanauchi et al., 2005; Kohama et al., 1990; Mirzaei et al., 2015; Rizk et al., 2018; Yu et al., 2002). Some of these studies provided the identification of putative bioactive peptides while others provided only peptide sequences with no association with biological activity, although they were also considered for analysis in the present study (Bener Aksam et al., 2013; Dasgupta et al., 2016).…”
Section: The Historical Use Of Yeast In Food Production—lessons From ...mentioning
confidence: 99%
See 1 more Smart Citation